2021
DOI: 10.51253/pafmj.v71i3.2940
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Findings in Patients Presenting for Upper Gastrointestinal Endoscopy at a Tertiary Care Hospital and the Influence of Age and Gender

Abstract: Objective: To determine the spectrum of findings in patients presenting for upper gastrointestinal (UGI) endoscopy and investigate role of age and gender. Study Design: Cross-sectional study. Place and Duration of Study: Department of Gastroenterology & Internal Medicine, Combined Military Hospital Kharian, from Jul 2017 to Mar 2019. Methodology: The data regarding 638 consecutive patients who underwent upper gastrointestinal endoscopy in the department were collected from the computer-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…This finding is in contrast to a previous study conducted among rural population in Hyderabad which reported squamous cell carcinoma of esophagus as the most common type of upper GI malignancy. 21 Such differences can possibly be explained by ethnic and geographical differences, requiring more in-depth analysis in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in contrast to a previous study conducted among rural population in Hyderabad which reported squamous cell carcinoma of esophagus as the most common type of upper GI malignancy. 21 Such differences can possibly be explained by ethnic and geographical differences, requiring more in-depth analysis in future studies.…”
Section: Discussionmentioning
confidence: 99%